(untitled) (IITM Journal of Business Studies, 2025)
This study investigates the innovative work behaviour of school teachers who practice in clusive leadership, with mediating roles of workplace friendship and psychological safety. Drawing on data from 308 school teachers, PLS-SEM revealed that inclusive leadership positively impacts innovative work behavior, workplace friendship, and psychological safety. Furthermore, both workplace friendship (WF) and psychological safety (PS) significantly in fluence innovative work behavior and serve as mediators in the relationship between IL and IWL innovative work behavior. The results ac centuate the importance of fostering inclusive leadership to enhance innovative work behav ior among educators, highlighting how work place friendships and psychological safety con tribute to creating an environment conducive to innovation. The study provides practical im plications for educational institutions to prior itize inclusive leadership practices and cultivate a supportive work atmosphere. By exploring these dynamics, the research offers valuable in sights into strategies for enhancing innovation in schools.